X a k 59 thus p n x x a n 1 dx n k 0 p k n a k x a k

This preview shows page 59 - 63 out of 67 pages.

We have textbook solutions for you!
The document you are viewing contains questions related to this textbook.
Power System Analysis and Design
The document you are viewing contains questions related to this textbook.
Chapter 5 / Exercise 5.8
Power System Analysis and Design
Glover/Overbye
Expert Verified
(xa)k.59
We have textbook solutions for you!
The document you are viewing contains questions related to this textbook.
Power System Analysis and Design
The document you are viewing contains questions related to this textbook.
Chapter 5 / Exercise 5.8
Power System Analysis and Design
Glover/Overbye
Expert Verified
ThusPn(x)(xa)n+1dx=nk=0P(k)n(a)k!(xa)kn1dx=nk=0P(k)n(a)k!(xa)kn1dx=n1k=0P(k)n(a)k!·(xa)knkn+P(n)n(a)n!ln|xa|+C.20.We look for the complex roots of the equationx2n=1 = cosπ+isinπ.tag1The roots areαk= cosφk+isinφk,¯αk= cosφkisinφkwherek= 0,1,2, . . . , n1, andφk=(2k+1)π2n. That means, we have exactly 2nrootsβj,j= 1,2, . . . ,2n,which areβ2k+1=αk,β2k+2= ¯αk,fork= 0,1,2, . . . , n. Therefore we haveP(x) :=x2n+ 1 = (xβ1)(xβ2). . .(xβ2n ) =:2nj=1(xβj).Since all the rootsβjare not repeating, there is the following (complex) partial fraction decompositionof1x2n+1:1x2n+ 1=2nj=0Cjxβj=2nj=1Cjm̸=j(xβm)2nm=1(xβm)=2nj=1CjP(x)P(βj)xβjP(x).Consequently,1 =2nj=1CmP(x)P(βj)xβ j.60
In the last equality, by passing to the limitxβm,m= 1,2, . . . ,2n, we obtain1 =Cm·limxβmP(x)P(βm)xβm=Cm·P(βm),i.e.Cm=1P(βm)=122n1m=βm22nm=βm2n.Therefore, we have1x2n+ 1=12n2nj=1βjxβj=12nn1k=0[αkxαk+¯αkx¯αk]=12nn1k=0αk(x¯αk) + ¯αk(xαk)(xαk)(x¯αk)=12nn1k=0x(αk+ ¯αk)2αk¯αkx2(αk+ ¯αk)x+αk¯αk=12nn1k=02xcosφk2x22 cosφk+ 1=12nn1k=0(xcosφk)2 cosφk+ 2 cos2φk2(xcosφk)2+ 1cos2φk=12nn1k=0(xcosφk)2 cosφk2 sin2φk(xcosφk)2+ sin2φk.Thusdxx2n+ 1=12nn1k=0cosφkln(x22xcosφk+ 1)+1nn1k=1sinφkarctan(xcosφksinφk)+C.21.(e): We apply the substitutiont12=x, 12t11dt=dxto get:dx(1 +4x)3x=12t11dt(1 +t3)t4= 12t7dtt3+ 1= 12∫ (t4t131t+ 1+13t+ 1t2t+ 1)dt=125t56t24 ln|t+ 1|+ 4t+ 1t2t+ 1dt=125x5126x164 ln(x112+ 1)+ 2 ln(x16x112+ 1) + 43 arctan(2x11213)+C.61
(g): SinceI:=3(x+ 1)2(x1)4dx=3x+1x1x21dx,we apply the substitutiont3=x+1x1,x=t3+1t31,dx=6t2dt(t31)2andx21 =(t3+ 1)2(t31)21 =4t3(t31)2.So, we getI=t(6t2)dt4t3(t31)2(t31)2=32dt=323x+ 1x1+C.(i): SinceI:=dxn(xa)n+1(xb)n1=nxbxa(xa)(xb)dx,we apply the substitutiontn=xbxa,x=tnabtn1,dx=ntn1(ba)(tn1)2dt, andxa=abtn1,xb=tn(ab)tn1.

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture